Development progress of coating first wall components with functionally graded W/EUROFER layers on laboratory scale. (22nd September 2020) - Emmerich, Thomas; Qu, Dandan; Ghidersa, Bradut-Eugen; Lux, Martin; Rey, Jörg; Vaßen, Robert; Aktaa, Jarir
Abstract: In the course of developing functionally graded tungsten/steel-layer systems as protective coatings for the first wall (FW) of future fusion reactors, an overview of the results attained so far is given. This includes the determined parameters for creating such systems by vacuum plasma spraying on a laboratory scale and the achieved material properties determined in previous works. To realize the coating of future full scale FWs as well, the coating process is adapted to larger coating areas in the form of mock-ups. For such components, special attention needs to be paid to the challenges of the limited temperature window during coating to achieve good coating adhesion, whilst avoiding exceeding the tempering temperature of the steel. One successfully coated mock-up is also exposed to fusion-relevant heat loads in HELOKA (Helium Loop Karlsruhe) to evaluate the coating system behavior and verify its durability. Finally, for even larger components the coating design and process are further optimized, supported by finite element simulations.